PERANAN ETIKA KERJA SEKRETARIS DALAM MEMBERIKAN PELAYANAN TERHADAP KINERJA AUDITOR PADA BAGIAN AKUNTAN NEGARA DI PERWAKILAN BPKP PROVINSI JAWA BARAT - Nur Azizah; Elen Septia Amelia; Sophia Rahmi; Agus Suherman (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2026)
Work ethics are a fundamental principle for secretaries in performing their duties professionally, maintaining the confidentiality of information, and supporting organizational service effectiveness. Within the Financial and Development Supervisory Agency (BPKP), secretaries play a strategic role in facilitating audit activities through administrative support, coordination, and the provision of accurate information. However, several issues related to the implementation of work ethics remain, including inadequate communication skills, limited concern for colleagues, and unprofessional behavior, which may affect the quality of services provided to auditors. This study aims to examine the role of secretarial work ethics in supporting auditor performance within the State Accountant Division at the Representative Office of BPKP of West Java Province. The study employs a descriptive research approach, with data collected through observation, interviews, and documentation. The findings are expected to demonstrate that the implementation of sound work ethics enhances the quality of secretarial services, facilitates the audit process, strengthens workplace relationships, and contributes to more effective and professional auditor performance.